Derecho a la no discriminación: mujeres migrantes e impacto de los medios de comunicación en Ibarra - Insuasti Torres, María Belén (2024)
The right to non-discrimination of migrant women in Ecuador is a fundamental issue that involves their vulnerability due to their gender and migratory status. The media plays a significant role in perpetuating or reducing discrimination towards these women. The general objective is to describe whether there is influence in the media on society's perception of migrant women in Ibarra. To achieve this, this research was conducted using a mixed approach that combined qualitative and quantitative elements. The level of descriptive depth allowed for examining and analysing previous research, theories, and relevant concepts related to the research topic. The methods applied included the socio legal method, which helped understand how the research topic relates to society and its legal environment. The analytical-synthetic method allowed for a deeper analysis and understanding of the various dimensions of the topic. The deductive method helped identify governmental actions and policies that could be related to the topic and provided valuable information about the political and administrative context in favor of the right to non-discrimination of migrant women due to media influence. The techniques used included documentary review, interviews with media outlets and migrant women, and surveys of society. As a result, it was found that the media in Imbabura does influence the perception of migrant women in Ibarra society, as 72.5% of the Ibarra population surveyed affirmed that the information conveyed by the media has influenced migrant women with discrimination, stereotypes, and xenophobia, violating their rights and hindering opportunities for advancement.